Segmentation and tracking of body parts for human activity recognition - Kristo. (2009)
Motion is an important cue for the human visual system. Current major goal of computer vision research is to recognize and understand human motion, activities and continuous activity. The research that was started on tracking a single person has nowadays grown into tracking, recognizing and understanding interactions among several people, like the scenes seen in MRT station or food courts. Interpreting such a scene with multiple interacting individuals is complex, because similar configurations may have different context and meanings. Understanding the complete meaning of an image sequence involving human interactions requires the thorough knowledge about the sequence, including the task of monitoring, inferring intention and ultimately interpreting the sequence.